Alcohol and falls among people with HIV infection: A view from Russia and the United States. (11th August 2022) - Kim, Theresa W.; Heeren, Timothy C.; Samet, Jeffrey H.; Bertholet, Nicolas; Lloyd‐Travaglini, Christine; Winter, Michael R.; Magane, Kara M.; Gnatienko, Natalia; Bryant, Kendall; Rateau, Lindsey J.; Muyindike, Winnie R.; Hahn, Judith A.; et al.
Abstract: Background: Both human immunodeficiency virus (HIV) infection and alcohol use predispose to autonomic/sensory neuropathy, imbalance symptoms, and cognitive impairment—conditions associated with a greater risk of falls—yet it is unclear how to identify people with HIV (PWH) whose drinking is associated with falls. Research on alcohol and falls using the same instruments in different countries could help to specify the level of alcohol use associated with fall risk. We examined whether a consumption‐based measure (the Alcohol Use Disorders Identification Test‐Consumption [AUDIT‐C]) and/or a symptom‐based measure (DSM‐5 criteria for alcohol use disorder [AUD]) are associated with sustaining a fall among PWH in St Petersburg, Russia and Boston, Massachusetts in the United States. Methods: Separate multivariate logistic regressions were used for each cohort to examine cross‐sectional associations for each alcohol measure predicting fall. Potential confounders included physical functioning, depressive symptoms, and other substance use (measured with the Addiction Severity Index). Results: A fall was reported by 35% (87/251) of the sample in Boston and 12% (46/400) in St Petersburg. Each additional AUD criterion—but not higher AUDIT‐C score—was significantly associated with a fall in both Boston (odds ratio [OR] = 1.10; 95% confidence interval [CI] 1.02, 1.18) and St Petersburg (adjusted OR AOR = 1.10; 95% CI 1.02, 1.18). Heavy alcohol use (>6 drinks/occasion, any vs. none) was associated with more than twice the odds of a fall (AOR = 2.24; 95% CI 1.21, 4.13) in Boston. Conclusions: These findings suggest that while fall risk may vary by setting and population, heavy alcohol use and AUD symptom severity are potential targets for interventions to prevent falls. Studies in diverse global settings advance our understanding of the relationship between alcohol and falls in PWH. Abstract : This study's findings suggest that each additional DSM‐5 criteria, a symptom‐based measure of alcohol use ‐ but not AUDIT‐C score – is significantly associated with a fall in 2 separate cohorts of people with HIV, one in Russia and the other in the U.S. Any heavy alcohol consumption was associated with more than twice the odds of a fall only in the U.S cohort. Heavy alcohol use and AUD symptom severity are potential targets for fall prevention.